Gene identification of recessively inherited Kaposi sarcoma in an Israeli and an Iranian family - Rinne, Sanni (My University, 2019)
Kaposi sarcoma is an inflammatory soft tissue tumor, which occurs in four different epidemiological forms: epidemic, iatrogenic, endemic and classic. Kaposi sarcoma is caused by an infection by Kaposi sarcoma-associated herpesvirus. However, the infection is not solely sufficient for the onset of the disease, but some degree of immune compromise is usually required. Familial clustering of classic Kaposi sarcoma is a rare event and no conclusive etiology behind it has been established. The aim of this study was to identify the possible genetic basis behind the familial form of classic Kaposi sarcoma in two consanguineous families: one from Iran and the other from Israel. The Iranian family had three affected individuals and the Israeli family had four. The inheritance model was hypothesized to be recessive based on the rarity of the cases and the inheritance pattern in the pedigrees. A genome-wide linkage analysis identified two shared regions in the Iranian family and 33 in the Israeli family. An extensive candidate variant analysis reduced the list of interesting candidate variants to one in the Iranian family and two in the Israeli family. Additionally, there were a number of non-coding variants with uncertain significance that could not be completely excluded. The best candidate in the Iranian family was a homozygous deletion of 9 kb in length, locating in the intron of a very poorly known lincRNA gene RP11-259O2.1. In the Israeli family, the two candidates were homozygous single nucleotide variants in the genes SCUBE2 and CDHR5. Both genes have been linked to cancer in some studies, but their specific biological functions are still largely a mystery. These results provide new information about the etiology behind the familial form of classic Kaposi sarcoma and a good base for further research.
Keywords: Kaposi sarcoma, Kaposi sarcoma-associated herpesvirus, Human herpesvirus 8, Whole genome sequencing, Genetic linkage, Long noncoding RNA